Entrepreneurial Intention among Malaysian Engineering Graduates: Male Versus Female - Abbas, Lutfiah Natrah (Journal of Technical Education and Training, 2015)
Engineering graduates are facing greater challenge to enter the limited job market in Malaysia and equipping graduates with entrepreneurial skills has been promoted as a potential solution to this issue. However, gender factor has been implicated in some studies to confound success of entrepreneurship courses.  The purpose of this study is to test the hypothesis of no difference between genders on entrepreneurial intention; a factor deemed to be important to entrepreneurship success. The Theory of Planned Behaviour (TPB) was selected as the framework for understanding this phenomenon.  Three hundred and twenty eight final year engineering students from one public technical university in Malaysia were selected for the study. The Entrepreneurial Intention Questionnaire (EIQ) was used to gather data on entrepreneurial intention among participants.  Using a t-test to analyse data on differences, no statistical difference in entrepreneurial intention is found between males and females, while slight difference is found in the components of TPB (attitude towards behaviour, subjective norm, and perceived behavioural control). The study suggests that gender may not be a factor that needs to be dealt with in the implementation of entrepreneurship programmes among engineering students.